Gender-stratified hierarchical modeling of patient and physician determinants of antihypertensive treatment outcomes: pooled analysis of seven prospective real-world studies with 17, 044 patients. (4th March 2021) - Hamarneh, Dina; Alkhatib, Nimer; Denhaerynck, Kris; Vancayzeele, Stefaan; Brié, Heidi; MacDonald, Karen; Abraham, Ivo
Abstract: Objective: Seven prospective real-world studies conducted in general practices in Belgium of antihypertensive treatment with valsartan-centric regimens were pooled to examine similarities and differences in determinants of blood pressure (BP) values (mmHg) and BP control rates between female and male patients. Methods: Pooled analysis of a total evaluable sample of 17, 044 patients, including 8273 (48.5%) women and 8771 men (51.5%) treated over approximately 90 days with valsartan-centric regimens in second or later line. Hierarchical linear and logistic regressions were applied to identify patient- and physician-related determinants of BP outcomes and a potential physician class effect. Results: Reductions in BP (mmHg) over 90 days were similar for women and men, and so were changes in BP control rates. Approximately a quarter of the variance in 90 day BP values was attributable to a physician class effect. Both gender groups shared some patient- and physician-related determinants of BP outcomes, though often varying in degree of influence. Analyses also revealed gender-specific determinants. Among others, modifiable/manageable patient-related determinants included BP at hypertension diagnosis (proxy for time of diagnosis), risk factors, antihypertensive treatment and adherence; while among the physician-related determinants clinical experience in hypertension treatment was modifiable/manageable. Conclusion: Valsartan-centric treatment regimens are associated with significant reductions in BP level and improvement in BP control in both women and men. The determinants revealed in modeling provide guidance to clinicians in the common and differential management of hypertension in female and male patients.